Pendidikan Agama Islam sebagai Upaya Pencegahan Radikalisme di Kalangan Pelajar - Agustina, Tessa; Tamara, Tiwi; Alfarizi, Angga; Sufriadi, Rahmat; Febryanto, Rahmad (Universitas Al-Qolam Malang, 2025)
The phenomenon of radicalism among students is a serious challenge in the context of Indonesian national education. This study aims to analyze the role of Islamic Religious Education (PAI) in forming moderate, tolerant, and nationalist characters in students as an effort to prevent radicalism. The method used is descriptive qualitative with case studies in several high schools in Bengkulu City, through observation, in-depth interviews with PAI teachers, and analysis of learning documentation. The results of the study indicate that PAI plays a strategic role in instilling the values of religious moderation through dialogical, contextual, and humanistic learning. PAI teachers actively integrate the values of tolerance, anti-violence, and national spirit in the learning process, and support religious activities that strengthen social solidarity and respect for diversity. Although there are obstacles such as a textual learning approach and lack of teacher training on the issue of radicalism, in general PAI is able to form students' ideological resilience against the infiltration of radicalism. This study recommends strengthening the curriculum of religious moderation, improving teacher competence, and collaboration between schools, families, and communities as effective strategies for preventing radicalism in the educational environment.